The value of the Makassar kelong in literature as an expression of local wisdom - Hajrah, Hajrah; Rosvita, Ita; Fitriansal, Fitriansal (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
This study aims to reveal the meanings contained in the oral tradition and modern form of kelong from Makassar, Indonesia. The research method is qualitative, using a literature review that focuses on cultural research. Data analysis uses the model developed by Miles and Huberman. Based on the results of the research, the value of Makassar kelong consists of: 1) religious values consisting of human relations with God, relations between humans, and human relations with the natural cosmos; 2) nationalism values consisting of love for the country, national spirit, respect for diversity, willing to sacrifice, and obey the law; 3) the value of independence consisting of hard work, creativity and innovation, discipline, resilience, lifelong learning; 4) the value of gotong royong which includes cooperation, solidarity, kinship, and mutual orientation; 5) and the value of integrity which includes honesty, exemplary, responsibility, and love of truth. The five kelong values reveal the function, implementation, and existence of local wisdom practiced by the people of Makassar today.